FEAR OF FALLING AND ASSOCIATED FACTORS AMONG OLDER ADULTS WITH KNEE OSTEOARTHRITIS AT VIET TIEP FRIENDSHIP HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the prevalence and identify factors associated with fear of falling among older adults with knee osteoarthritis at Viet Tiep Friendship Hospital in 2025.Methods: A cross-sectional descriptive study was conducted from March to October 2025 among 113 older adults diagnosed with knee osteoarthritis. Convenience sampling was applied at the outpatient clinic.The average FES-I score was 42.21 ± 13.83Results: The majority of participants had a high level of fear of falling (74.3%), with average FES-I score was 42.21 ± 13.83. Univariate analysis showed that sex, history of falls, physical function, use of assistive devices, and fall risk were significantly associated with high fear of falling (p < 0.05). In multivariate logistic regression, only sex (aOR = 3.05; 95% CI: 1.19-7.86; p = 0.02) and fall risk (aOR = 5.17; 95% CI: 1.54-17.33; p = 0.008) remained independently associated factors.Conclusion: Fear of falling among older adults with knee osteoarthritis was high and significantly associated with sex and fall risk. Targeted screening and fall-prevention interventions are needed to improve psychological well-being and physical function in this population.
Keywords: Fear of falling, older adults, knee osteoarthritis, fall risk.